Erosion Mitigation via Bio-Mediated Soil Improvement - Dubey, Anant Aishwarya (Curtin University, 2022)
In the present study, the biocementation potent bacteria were isolated from the soil of the Brahmaputra River basin based on the hypothesis that soils are rich in microbial biodiversity. A novel biopolymer-biocement composite was also proposed. The efficacy of biocementation to mitigate soil erosion was studied via lab-scale simulation of aeolian, riverbank and coastal erosion. This study provides solid evidence for substantial improvement in soil erodibility resistance with biocementation.